Pemanfaatan Koro Pedang Sebagai Bahan Baku PembuatanDadih Dengan Penambahan Susu Dan Pewarna AlamiMelalui Lama Pemeraman Yang Berbeda - Azizah, Ummu, Dra. Aminah Asngad M.Si (2017)
Curd that is traditional food that comes from South Sumatera made from curd that fermented in bamboo then covered with banana leaves. Defeloping of curd be one of the commercial product that can be done throught the replacement of card by using grain, like as soy beans, green peas, red peas, and koropedang. The process of fermentation curd during 48 hours with the help bacteria acid laktat (BAL) are there in bamboo so that will be formed curd and whey. This research aim to know the quality of curd koropedang with the addition of natural coloring extract the skin of the dragon fruit. This research methot using a Complete Randomized Design (RAL) by a factor of 2 and 9 treatment i.e the type of milk (J) and (L) the curing of gold, the addition of cow's milk and goat's milk by as much as 60 ml 140 koropedang treatment on each except on 200 ml control with long curing 42 hours, 48 hours, and 58 hours. The curd jack bean have levels of 50,02 g on J1L2 (the addition of cow's milk by as much as 60 ml). curd products most dominant white bone, flavorful typical of koropedang has a sour taste with a rough texture and the power of the dominant panelists like the treatment received was J2L1.